Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.4314/ejb.v16i1.7
|View full text |Cite
|
Sign up to set email alerts
|

The stimulating impact of elevated temperatures on growth and productivity of <i>Parthenium hysterophorus</i> L.

Abstract: Invasive alien weeds pose a great threat to biodiversity by suppressing the native flora and causing negative impacts on crop yields. Parthenium hysterophorus is an exotic weed that causes nuisance and health hazard to mankind and animals, and is a danger to the environment. Experiments were conducted during summer and winter to understand the impact of different temperature conditions on the growth of Parthenium. Pot studies conducted at 22-30 0 C temperature conditions were considered as control. During summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…For parthenium, the no. of branches (8/plant) and capitula (288/ plant) produced per plant were more in summer when compared to winter (5/plant and 239/plant, respectively) (Kapoor, 2014). This study is supported by Toh et al (2011) and reported that increased temperature enhances the growth of parthenium, enlarges canopy size and structure and accelerates population growth rate because of the shortened life cycle.…”
Section: Weeds and Their Management Under Changing Climate: A Reviewsupporting
confidence: 80%
“…For parthenium, the no. of branches (8/plant) and capitula (288/ plant) produced per plant were more in summer when compared to winter (5/plant and 239/plant, respectively) (Kapoor, 2014). This study is supported by Toh et al (2011) and reported that increased temperature enhances the growth of parthenium, enlarges canopy size and structure and accelerates population growth rate because of the shortened life cycle.…”
Section: Weeds and Their Management Under Changing Climate: A Reviewsupporting
confidence: 80%
“…Values obtained are given from (Kapoor, 2014). Mominul Islam, 2014, isolated the phytotoxic substance, suaveolic acid (14α-hydroxy-13β-abiet-8-en-18-oic acid), from H. suaveolens and reported that at concentrations greater than 30 μM, suaveolic acid found to exhibit phytotoxicity against the shoot and root growth of garden cress, Italian ryegrass, and barnyard grass and lettuce shoots.…”
Section: Resultsmentioning
confidence: 99%
“…Gray; 55 μL L −1 ), which might be responsible for parthenium weed's superior ability to tolerate stomata closure under strong heat and light conditions, particularly during early stages of the plant life cycle (Moore et al 1987). As adult plants, parthenium weed grown under natural conditions during the summer (35 to 45 °C) exhibited an increased growth rate, leaf chlorophyll content, total soluble sugar, and protein content than plants grown under a cooler temperature range (22 to 30 °C) in a glasshouse (Kapoor 2014). Furthermore, hightemperature exposure caused a substantial increase in the biosynthesis of protective antioxidants, such as peroxidase and superoxide dehydrogenase, in parthenium weed plants (Sharma et al 2014).…”
Section: High Temperaturesmentioning
confidence: 99%